STRATEGI ADAPTASI SIMBOLIK PEMBATIK YANG TERMARGINALKAN TERHADAP HEGEMONI PASAR - Casta, Casta (Indonesian Journal of Conservation, 2018)
The structure of Trusmi-Cirebon batik actors release some entrepreneurs who have capital strength which hegemony the market and the marginalized craftsman. This study aimed to understand the hegemony patterns of batik market and symbolic adaptation strategies of artisans who are marginalized in the creation of designs, marketing, and interpreting internal conflicts. Research used a qualitative approach using a type of phenomenological research. The results of this study showed that the market hegemony was carried out by showroom, produced batik with thecategory of anggon batik, the used of silk materials, and adapted to market interest. On the other hand, marginalized craftsman of Trusmi batik face the hegemony of batik market by carried out the design creation strategy by making batik with the category of obrogan, made a typical of traditional batik motifs, not used silk and another similar materials, avoided showrooms market, and used the service of pengeber, yarnen and yarlud. They choose to avoid internal conflicts by considering batik as a joint property which was an ancestral heritage. It was concluded that the symbolic adaptation strategy of marginalized craftsmen was conducted to maintain the balance (homeostasis), order, and social integration